Repetitive transcranial magnetic stimulation and constraint-induced movement therapy combined in the treatment of post-stroke movement disorders: a narrative review - Liu, Zhennan; Yu, Qingying; Zhou, Feng; Yu, Muyao; Shu, Huan; Zhu, Manhua; Peng, Tianzhong (Frontiers in Human Neuroscience, 2025)
Stroke is a significant cardiovascular and cerebrovascular condition and is among the primary causes of prolonged neurological impairment globally. Approximately 55%–75% of stroke survivors will experience some form of long-term sensorimotor impairment. Post-stroke, the upper limb typically exhibits restricted mobility, complicating daily chores for 70% of patients and impairing normal limb utilization. Repetitive Transcranial Magnetic Stimulation (rTMS), a prominent non-invasive neuromodulation technique designed to enhance functional recovery post-stroke, has garnered significant attention in clinical studies. Likewise, constraint-induced movement therapy (CIMT) has been extensively employed in therapeutic settings to promote neuroplasticity. However, there remain several issues with it in practical application. Recently, considerable focus has been directed toward a novel treatment known as rTMS in conjunction with obligatory motor therapy. This can circumvent the issues associated with conventional treatments and optimize the advantages of both. This article discusses the present status of clinical research with rTMS and CIMT.